Bioavailability of Isothiocyanates From Broccoli Sprouts in Protein, Lipid, and Fiber Gels. Issue 18 (14th April 2018) - Oliviero, Teresa; Lamers, Simone; Capuano, Edoardo; Dekker, Matthijs; Verkerk, Ruud
Abstract : Scope: Optimization of bioavailability of dietary bioactive health‐beneficial compounds is as important as increasing their concentration in foods. The aim of this study is to explore the change in bioavailability of isothiocyanates (ITCs) in broccoli sprouts incorporated in protein, fiber, and lipid gels. Methods and results: Five participants took part in a cross‐over study and collected timed urine samples up to 24 h after consumption of proteins, dietary fibers, and lipid gels containing broccoli sprouts powder. Sulforaphane and iberin metabolites were determined in the urine samples. Samples in which sulforaphane and iberin were preformed by myrosinase led to a higher bioavailability of those compounds. Compared to the control broccoli sprout, incorporation of sprouts in gels led to lower bioavailability for preformed sulforaphane and iberin (although for sulforaphane the lower bioavailability was not significantly different) whereas for the gels rich in their precursors, glucoraphanin and glucoiberin, the opposite trend was observed (although not significantly different). Conclusion: This explorative study suggests that ITCs bioavailability can be modulated by food structure and composition and further and deeper investigations are needed to develop food products that lead to an optimized ITCs bioavailability. Abstract : Optimization of bioavailability of health‐beneficial compounds is as important as increasing their concentration in foods. In this study, the effect of proteins, fibers, and lipids on the bioavailability of isothiocyanates from broccoli sprouts is explored. This study suggests that isothiocyanate bioavailability could be modulated by food structure and composition, and further investigations are needed to develop food products that lead to optimized bioavailability.